The DFA/DFT‐based hacking techniques and countermeasures: Case study of the 32‐bit AES encryption crypto‐core. Issue 2 (2nd March 2021) - Karmani, Mouna; Benhadjyoussef, Noura; Hamdi, Belgacem; Machhout, Mohsen
Abstract: Integrated circuits (ICs) design plays a significant role in the embedded‐system performance, reliability and security. Thus, the constant advances in very large‐scale integration technology have led to design and manufacture of very complex ICs based on the System on a Chip (SoC) approach design. Therefore, the embedded system testing is considered earlier during the design process and testability is used as one of the objectives for evaluating safety‐critical embedded system designs. On the other hand, embedded systems used in critical applications execute security‐critical commands and collect sensitive data protected by cryptographic keys and authentication codes. The data and the unauthorised access of these embedded devices is an obvious target for attackers in order to obtain control or extract internal data. In this paper we consider that by using Design for Testability (DFT) approaches an attacker can control and affect a security‐critical embedded system. Thus, the authors focus on the DFT approach, as a means of violation of the security and confidentiality of embedded systems with security‐critical goals. In addition, with or without insertion of DFT circuitry, the crypto‐core is always exposed to the powerful differential fault analysis (DFA) attack. Here, a 32‐bit AES crypto‐core is used as a case study in order to analyse the DFA‐ and the DFT‐based Hacking techniques. A countermeasure was performed in order to avoid any scan or even DFA attack attempt.